Gas Exhibits Building, New York World's Fair 1939 (Grinnell Litho Co.)
Four ninety-foot pylons form a unique entrance to the building through a circular Court of Flame. Several hundred gas corporations have united to make this one of the most interesting displays in the Community Interests Zone.